2013
DOI: 10.1038/gim.2013.13
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of brachytelephalangic chondrodysplasia punctata: identification of arylsulfatase E mutations, functional analysis of novel missense alleles, and determination of potential phenocopies

Abstract: Brachytelephalangic chondrodysplasia punctata (BCP) describes a group of heterogeneous conditions with overlapping phenotypes. X-linked recessive BCP (CDPX1) (OMIM no. 302950), originally recognized by Sheffield et al., 1 is a panethnic congenital rare disorder that affects males. The most characteristic clinical features are as follows: 2,3 (i) Chondrodysplasia punctata, or stippled epiphyses, observed on X-ray. These minimally involve the ankle and distal phalanges but can also include long bones, vertebrae,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Some cases were described with only shortened distal phalanges and mild midfacial hypoplasia [ 1 ]. Delayed motor and cognitive development are reporeted in 19–33 % and 16–20 % of cases, respectively [ 3 , 6 ]. Also, fertility is normal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some cases were described with only shortened distal phalanges and mild midfacial hypoplasia [ 1 ]. Delayed motor and cognitive development are reporeted in 19–33 % and 16–20 % of cases, respectively [ 3 , 6 ]. Also, fertility is normal.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to genetic cause, important maternal etiological factors have been linked to the phenotype (warfarine exposure, vitamin K deficiency, maternal autoimmune disease), but still around 40 % of male patients with brachytelephalangic chondrodysplasia punctata do not have detectable ARSE mutations or known maternal etiological factors [ 3 , 6 ]. Further understanding of mechanism behind ARSE function might prove useful in identifying other potential candidates in the same disturbed pathway that, when defective, would lead to the similar phenotype of brachytelephalangic chondrodysplasia punctata.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, 8 years later, the same group reported a female with the same condition and raised the possibility that BCDP is genetically heterogeneous (Peter et al, 1997). Further reports showed that 58% of the males with this phenotype carry pathogenic variants in the ARSE located at Xp22.33 (Matos‐Miranda et al, 2013), and the rest are probably the result of an evolving group of genetic aetiologies including Keutel syndrome (MIM# 245150), VKORC1 ‐related warfarin resistance (MIM# 122700) and other conditions yet to be identified. The possibility of maternal autoimmune condition was raised as an acquired cause but has not been investigated in the era of next generation gene sequencing (Chitayat et al, 2008).…”
Section: Introductionmentioning
confidence: 99%